Effect of vermicompost on the nutraceutical quality of tender cladodes of Opuntia ficus-indica - Lugo-Palacios, Raúl Eduardo; Lugo-Palacios , Aaron David; Luna-Ortega, J. Guadalupe; Zuñiga-Valenzuela, Rafael; Ramírez-Aragón, Mercedes Georgina (Journal of the Professional Association for Cactus Development, 2024)
The consumption of tender cladodes knows as “nopalitos” (Opuntia ficus-indica L. Miller.) has increased worldwide. That is because it is an important nutritional source in the human diet given its content of fiber, minerals, vitamins, phenolic compounds and secondary metabolites (antioxidants, phenols and flavonoids), which are essential for human health. The objective of this study was to evaluate the effect of doses of vermicompost (0, 5, 15 and 25 t ha-1) on the yield and nutraceutical quality of tender cladodes of O. ficus-indica. The measured variables were tender cladodes production and nutraceutical quality. The results showed no significant effect on the content of total phenolic compounds, total flavonoids and antioxidant capacity. However, the application of vermicompost showed significant effects on the yield, in which higher estimates were achieved for the highest dose with up to 100% compared to the control. The data obtained indicate that the dose of 25 t ha-1 of vermicompost promotes and increase in yield without compromising the nutraceutical quality of “nopalitos”.